Expert Consensus for Rehabilitation of Traditional Chinese Medicine in Perioperative Period of Total Hip Replacement - Working group on setting up guidelines for diagnosis and treatment of hip dysfunction in orthopedics section of Chinese Medicine Society (康复学报)
In order to popularize the related concepts of perioperative rehabilitation evaluation and treatment for hip replacement, standardize the technical operation procedure and promote the development of orthopedics rehabilitation discipline, promote the development of orthopedic rehabilitation disciplines, combined with literature research, based on the basic principle, the expert group repeated demonstration, made"Expert consensus for rehabilitation of traditional Chinese medicine in perioperative period of total hip replacement". The expert consensus emphasizes the importance of preoperative education and postoperative guidance, and integrates the traditional Chinese medicine syndrome differentiation, acupuncture analgesia, xueweiyadou, and so on into the rehabilitation program. Follow the principles of strength training, joint activity training, weight training on the basic principles, specific training methods recommended within six weeks after operation, according to the four stages step by step, at the same time, postoperative rehabilitation training suggestions under the guidance of at least continue to twelve weeks.